Solutions of the Dirac Equation in a Magnetic Field and Intertwining Operators - Contreras-Astorga, A.; J. Fernández C., D.; Negro, J. (Symmetry, Integrability and Geometry: Methods and Applications, 2012)
The intertwining technique has been widely used to study the Schrödinger equation and to generate new Hamiltonians with known spectra. This technique can be adapted to find the bound states of certain Dirac Hamiltonians. In this paper the system to be solved is a relativistic particle placed in a magnetic field with cylindrical symmetry whose intensity decreases as the distance to the symmetry axis grows and its field lines are parallel to the x−y plane. It will be shown that the Hamiltonian under study turns out to be shape invariant.